Ionic Liquid-Based Electrolytes for Calcium-Based Energy Storage Systems. Issue 10 (23rd June 2020) - Stettner, T.; Dugas, R.; Ponrouch, A.; Balducci, A.
Abstract : In this work, aprotic and protic ionic liquid (IL)-based electrolytes designed for calcium-based energy storage systems are investigated. We have shown that these electrolytes display good transport properties and electrochemical stabilities comparable with those of IL-based electrolytes proposed for lithium and sodium-based systems. The use of these electrolytes in electrochemical double layer capacitors (EDLCs) leads to the realization of devices displaying good capacitances paired with a high reversibility and stability. Their use in combination with TiS2 cathode appears more problematic as the cation of the ILs is inserting in the layered structure of this material during the charge process. In this latter case a careful design of the cation appears necessary to guarantee selective insertion of Ca 2+ and reversible charge-discharge process.